An Empirical Analysis of The Phenomenon of Initial Public Offering Underpricing in The United States Stock Market (2010 – 2012) - Xiao, Yang (2014)
Numerous studies prove that initial public offerings (IPOs) of common stocks are priced at a discount relatively to the closing price in first trading day. Many explanatory hypotheses and models have been advanced to explain this phenomenon. The global financial crisis of 2007 - 2009 result in unprecedented decrease in the number of IPOs in the U.S. market during the crisis time and this number have restored to the record level before financial crisis since 2010. Using a sample of 232 firms went public from 2010 – 2012, this paper (i) records the level of IPO underpricing during the sample period, and (ii) investigate how the explanatory theories and models developed before financial crisis time can be used to explain IPO underpricing over the period of interest. After excluding several control variables, a model with the best fitness to the data set and the greatest explanatory power is selected by utilizing AIC method. The empirical results show that winner’s curse model, signaling hypothesis and partial adjustment phenomenon are the main factors account for the IPO underpricing throughout the three years period (2010 to 2012) after the global financial crisis of 2007 – 2009.